1999
DOI: 10.1111/j.1749-6632.1999.tb11332.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic Modulation of Glutamate and GABA Synaptic Transmission in Hippocampal Neurons

Abstract: Although the hippocampus expresses nicotinic acetylcholine receptors (nAChRs) and receives cholinergic innervation, the functional roles of these receptors are not completely understood. Our results indicated that presynaptic nAChRs mediated a calcium influx that enhanced the release of both glutamate and GABA. Fura-2 detection of calcium in single mossy fiber presynaptic terminals indicated that nAChRs directly mediated a calcium influx. In hippocampal neurons in primary culture, both spontaneous vesicular re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
126
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(135 citation statements)
references
References 61 publications
7
126
2
Order By: Relevance
“…In addition, nAChRs can modulate GABAergic transmission in multiple brain areas, such as thalamus, cortex, hippocampus, and interpeduncular nucleus (Lena et al, 1993;Alkondon et al, 1997Alkondon et al, , 2000Lena and Changeux, 1997;Fisher et al, 1998;Radcliffe et al, 1999). Modulation of GABA neurons by nAChRs has been most extensively studied in the hippocampus, where GABAergic interneurons express multiple nAChR subtypes (Alkondon et al, 1997;Jones and Yakel, 1997;Frazier et al, 1998b;McQuiston and Madison, 1999;Ji and Dani, 2000).…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, nAChRs can modulate GABAergic transmission in multiple brain areas, such as thalamus, cortex, hippocampus, and interpeduncular nucleus (Lena et al, 1993;Alkondon et al, 1997Alkondon et al, , 2000Lena and Changeux, 1997;Fisher et al, 1998;Radcliffe et al, 1999). Modulation of GABA neurons by nAChRs has been most extensively studied in the hippocampus, where GABAergic interneurons express multiple nAChR subtypes (Alkondon et al, 1997;Jones and Yakel, 1997;Frazier et al, 1998b;McQuiston and Madison, 1999;Ji and Dani, 2000).…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%
“…The physiologic impact of nAChR activation is critically dependent upon their localization. There is evidence for nAChR expression both on presynaptic terminals, where they directly modulate GABA release, independent of action potential firing (Fisher et al, 1998;Lu et al, 1999;Radcliffe et al, 1999), and away from the synaptic terminal, where modulation of GABA release is TTX sensitive (Alkondon et al, 1997(Alkondon et al, , 2000Frazier et al, 1998b). The nAChR-induced modulation of GABAergic transmission in VTA is TTX sensitive, suggesting that the receptors are not expressed on the terminals per se.…”
Section: Nicotinic Modulation Of Gabaergic Transmission In the Vtamentioning
confidence: 99%
“…These conclusions have been drawn from the following findings: (i) field evoked-glutamatergic transmission between Schaffer collaterals and CA1 neurons is facilitated by 30 nM ACh and inhibited by 30 M ACh, and (ii) the nAChR antagonists MLA and DH␤E facilitate glutamatergic transmission between the Schaffer collaterals and CA1 pyramidal neurons. Facilitation of glutamatergic transmission by low level of ␣7 nAChR activation induced with 30 nM ACh is likely the result of increased intracellular Ca 2ϩ concentrations (see Radcliffe et al, 1999;Albuquerque et al, 2000, and references therein). In contrast, inhibition of synaptic transmission by 30 M ACh is probably the result of ␣7 nAChR activation to a degree that causes enough depolarization to inactivate Na ϩ channels and inhibit the active propagation of action potentials (Alkondon et al, 2000a).…”
Section: Therapeutic Significance Of Nicotinic Aplsmentioning
confidence: 99%
“…More recently, in two different neuronal preparations, a7 n-AChRs have been shown to be preferentially located at extrasynaptic site, activated by the spillover of ACh released at the active site (Jones and Wonnacott, 2004;Coggan et al, 2005). A large number of studies have demonstrated that a7 n-AChR stimulation can increase both glutamate and GABA release in a number of brain structures, including the hippocampus (Gray et al, 1996;Radcliffe et al, 1999;Reno et al, 2004). Furthermore, the activation of presynaptic a7 n-AChRs may trigger hippocampal ACh release from septal projections, consistent with the presence of a7 n-AChR mRNA in septohippocampal cholinergic neurons (Azam et al, 2003;Strong et al, 2003).…”
Section: Introductionmentioning
confidence: 99%